Position Improvement Strategy for Balinese Tourism Human Resources to Manager Level in Rated Hotels in Bali - Sulistyawati Sulistyawati (Journal of Business on Hospitality and Tourism, 2015)
Creating superior Indonesian tourism requires that it be managed by tourism human resources who are qualified and professional in their field. Pitana (2011) stated that Indonesian tourism human resources are of sufficient quality. On the other hand, Pangestu (2012) asserted that although national tourism has shown growth with increasing competitiveness rankings, yet Indonesian tourism is still inferior when compared to neighboring countries. Bali, as a quickly growing tourist region, has become a magnet for job seekers from other provinces, even foreigners. This, of course, is an ironic matter for local human resources in terms of competing to occupy managerial positions. Problems taken up were: 1) what are the obstacles faced by Balinese tourism human resources in order to be able to occupy manager positions at rated hotels in Bali, and 2) how is the strategy for increasing the number of Balinese tourism human resource manager positions at rated hotels in Bali. This research aimed to produce a model strategy for improving the position of Balinese tourism human resources to the level of manager at rated hotels in Bali. An exploratory sequential mixed method with qualitative to quantitative data was used through interviews with fourteen informants who are managers at rated hotels in Sanur, Nusa Dua, and Kuta and tourism practitioners and academics as well as questionnaires. Data analysis applied competence theory (Spencer & Spencer, 1993), hegemony theory (Gramsci, 1971), and motivation theory (Clelland, 1976). The research results show six informants stated that the number of Balinese tourism human resources who occupy manager positions is still low. Meanwhile, eight informants stated the opposite. The results of the research analysis are: 1) the cause of Balinese tourism human resources not being selected for manager positions are: (a) underestimation of Balinese tourism human resources; (b) low competitiveness; (c) politicization of positions; (d) adat (customary) commitments; and (e) lack of mobility. And, 2) a strategy to increase positions can be carried out by: (a) providing opportunities for achievement; (b) creating a cooperative atmosphere; and (c) providing opportunities for status improvement.